Evaluating gun policy : effects on crime and violence - Ludwig, Jens; Cook, Philip J., 1946- (Brookings Institution Press, 2003)
Annotation Policymakers have tried to combat gun-related violence and crime in various ways: including sentence enhancements, restricting access, and banning certain models and designs. Yet far too little is currently known about the efficacy of these policies. This book sheds light on what works by presenting rigorous empirical evaluations of a variety of current policies.
Keywords: Gun control -- United States.; Violent crimes -- United States.; Armes à feu -- Contrôle -- États-Unis.; Crimes violents -- États-Unis.; TRUE CRIME -- General.; POLITICAL SCIENCE -- Civil Rights.; Gun control; Violent crimes; United States